Strategi Efektif bagi Widyaiswara: Analisis Hambatan dan Solusi untuk Meningkatkan Produktivitas Publikasi Ilmiah Widyaiswara - Sutrisno Heru Sukoco; Naily Kamaliah; Alpha Fadila Juliana Rahman (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2024)
This research aims to analyze the obstacles and solutions faced by educators (widyaiswara) in improving the productivity of scientific publications. The research method employed is analytical descriptive, utilizing online questionnaires for data collection. The primary respondents are 40 educators participating in scientific publication pilot training. Data analysis involves descriptive statistics, multinomial logistic regression, and Fisher exact test. The research findings indicate that 50% of educators mention time constraints, 17.5% cite laziness, and 15% identify a lack of references as obstacles. The proposed solutions to overcome these obstacles involve the utilization of artificial intelligence (AI) technology. Regarding the use of references in scholarly literature, educators are deemed proficient in selecting reference sources. However, there is room for improvement in the optimal utilization of scientific reference tools, with 66% of educators not yet utilizing reference management applications in their scientific publications. This research provides insights into challenges and recommended solutions for enhancing the productivity of scientific publications for educators. The promotion of AI utilization, modern applications, and tools for academic reference searches needs continuous advocacy. Participation in training, joining Communities of Practice (CoP), and self-directed learning in scientific writing can serve as solutions for educators to boost motivation and improve the quality of their research and resulting publications.